Important Aspects in the Application of Composite Materials and New Methods of Application - Azimov Sarvarbek Qayumjon ugli; Yusupov Bunyodbek Abdukarim ugli; Madina Zarbotova Qaxromon qizi (Zien Journals, 2023)
This article describes the methods of applying composite materials, new application processes, disadvantages and solutions to it.
Keywords: Composite materials,; ferrous metals; dispersion-compacted,; plastic